2010
DOI: 10.1021/jp100530m
|View full text |Cite
|
Sign up to set email alerts
|

Q(n) Species Distribution in K2O·2SiO2 Glass by 29Si Magic Angle Flipping NMR

Abstract: Two-dimensional magic angle flipping (MAF) was employed to measure the Q((n)) distribution in a (29)Si-enriched potassium disilicate glass (K(2)O.2SiO(2)). Relative concentrations of [Q((4))] = 7.2 +/- 0.3%, [Q((3))] = 82.9 +/- 0.1%, and [Q((2))] = 9.8 +/- 0.6% were obtained. Using the thermodynamic model for Q((n)) species disproportionation, these relative concentrations yield an equilibrium constant k(3) = 0.0103 +/- 0.0008, indicating, as expected, that the Q((n)) species distribution is close to binary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 40 publications
4
45
0
Order By: Relevance
“…1 correlates a t 1 dimension containing both isotropic and anisotropic frequencies to a t 2 dimension containing only isotropic frequencies, as presented in previous MAF investigations of silicate glasses [12][13][14]. The 2D MAF spectra presented here, however, have been transformed to correlate a purely isotropic spectrum to a purely anisotropic spectrum through the application of an affine transformation [36], consisting of a shear parallel to t 2 using a shear factor of 1.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…1 correlates a t 1 dimension containing both isotropic and anisotropic frequencies to a t 2 dimension containing only isotropic frequencies, as presented in previous MAF investigations of silicate glasses [12][13][14]. The 2D MAF spectra presented here, however, have been transformed to correlate a purely isotropic spectrum to a purely anisotropic spectrum through the application of an affine transformation [36], consisting of a shear parallel to t 2 using a shear factor of 1.…”
Section: Methodsmentioning
confidence: 94%
“…This approach applied to one-dimensional static sample NMR spectra, however, is limited by low sensitivity and strong overlap of anisotropic lineshapes for different Q (n) -species. In previous works [12][13][14], we demonstrated that Magic Angle Flipping (MAF) [15], which is a 2D NMR experiment capable of correlating the isotropic and anisotropic frequency contributions of the nuclear shielding along two orthogonal dimensions, provides an order of magnitude improvement in quantifying Q (n) -species compared to fitting 1D static or MAS NMR lineshapes alone. This 2D NMR approach has been successfully applied in quantifying the relative populations of Q (n) in silicate glasses of composition 2Na 2 O·3SiO 2 [12], K 2 O·2SiO 2 [13], and CaO·SiO 2 [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we can hypothesize that the following reaction (Eq. (2)) also occurs in the materials and provides other silica oligomers [34]:…”
Section: Discussionmentioning
confidence: 99%
“…4 is an example of the application of the TOP processing applied to a 2D signal, S top ð; tÞ, constructed from the 29 Si NMR Hahn echo signal of polycrystalline Clinoenstatite. Clinoenstatite has two inequivalent tetrahedrally coordinated (i.e., Q (2) ) silicon sites, resolved at À85.2 ppm and À82.8 ppm in the isotropic dimension, and exhibit similar nuclear shielding anisotropies, as expected [24,25], in the sideband dimension.…”
Section: Topmentioning
confidence: 92%